Penerapan Model Pembelajan Contextual Teaching Learning (CTL) Dalam Mata Pelajaran PAI di SMP Negeri 2 Koto Baru - Yiyin Aitu Mulia; Puti Andam Dewi; Siswanto S (Penerbit Yayasan Daarul Huda Kruengmane, 2023)
This research aims to create learning that is fun and easy to understand, by using varied learning models it can reduce student boredom when studying and can increase student motivation to learn. That way the teaching and learning process in class will be more effective. This research uses a classroom action research model, where teachers directly carry out teaching practice at SMP N 2 Koto Baru class VIII D using student worksheets. This research is casuistic in nature and has a context on the conditions, circumstances and situations that exist in the classroom which are carried out to solve problems that occur in order to improve the quality of learning in the classroom. This research discusses the context of the contextual teaching and learning (CTL) learning model, the steps for using the CTL learning model, as well as the implementation of the CTL learning model in class VIII D. Based on the author's observations, students seemed enthusiastic in discussions and doing homework on the LKPD. Because it is assisted by learning media in the form of PowerPoint and LKPD to draw conclusions from each material and process it so that it is easy for students to understand.